Teachers’ Managing of Learning English Online During Covid- 19 Pandemic - Maulida Rizkina, Nina Afrida & Wahidah (JADEs Journal of Academia in English Education, 2022)
The impact of the covid-19 pandemic is not only felt in the world of health but also has an effect on the world of education. This phenomenon makes teachers use a variety of online learning applications to meet cognitive, affective, and social in learning. The purpose of this study is to find out how English teachers manage online English learning. Various institutional and educational creativities use online media with different platforms to facilitate students. This research method uses a descriptive of qualitative research. With the object of research is teacher. The researcher used 2 instruments in collecting data. There are interview and questionnaire. The result this study of Teachers ‘managing English online as follow :(1) teachers manage English online learning using application such as WhatsApp group, google classroom, zoom meeting. (2) teachers give the rule in English online learning. (3) teachers prepare the material for learning (4) teachers make discussion with the student) based on data from interview (5) teacher give student the material early.